Participation of Women in Decision-making and Land Use: A Case of Vegetable Farming in Chitwan, Nepal - Shrestha, Rashmi; Bhatta, Sushmita; Mishra, Binayak Prakash (Journal of Agriculture and Forestry University, 2025)
This study examines women’s participation in decision-making and land use in vegetable farming in Chitwan, Nepal. Primary data were collected from 100 randomly selected female vegetable farmers through household surveys using a semi-structured interview schedule. Descriptive statistics, primarily frequency distribution, were used for data analysis. Results indicate that women contribute significantly across almost all stages of vegetable production; however, their decision-making autonomy is constrained in critical areas such as crop planning, leasing, and land allocation, where male or joint authority remains dominant. Although 41% of respondents independently managed household income and 29% made decisions regarding rented land, only 18% possessed legal land titles. Barriers to greater participation included low levels of education, limited access to agricultural information, inadequate land rights, and heavy time burdens. Only 36% of women had received agricultural training, mostly through cooperatives. Despite these challenges, 83% expressed willingness to remain involved in land-use decisions, largely due to family welfare, farming expertise, and financial necessity. Furthermore, 79% of respondents lacked awareness of available support programs, underscoring gaps in institutional outreach. The findings reveal persistent structural inequalities in women’s formal authority and emphasize the need for policies promoting equitable access to resources, training, and legal land rights.